[Marcos pa rin ; Freedom Island ; New beginning [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
A debate on the return of the dead body of Ferdinand Marcos to the Philippines. Focuses situation of the residents in the Freedom Island also called Pulong Maria when they will be relocated. Takes a look at the career of Nora Aunor and the cancellation of her program in TV.